PHARMACEUTICO-ANALYTICAL STUDY OF NIRGUNDIGHRITA AND EVALUATIONOF ITS ANTIOXIDANT AND ANTIMYCOBACTERIAL ACTIVITY W.R.T. TUBERCULOSIS: A STUDY PROTOCOL (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: In Ayurveda, Rajyakshma (Tuberculosis) is mainly caused due to Oja kshay (lack of immunity). Nirgundi ghrita is Sneha kalpa that contain two ingredients which are panchang of Nirgundi (Vitex negundo Linn.) and Ghrita. Nirgundi ghrita is a formulation mentioned in Chakradatta for the treatment of Yakshma (Tubeculosis). It is mentioned in the text that consumption of Nirgundi ghrita will leads in improvement in the immunity of the person. Need of the Study: In view of the properties of Nirgundi and Ghrita, evaluation antioxidant effect and anti-mycobacterial activity of formulation Nirgundi Ghirta in Tuberculosis is needed. Aim: Pharmaceutico-analytical study of Nirgundi ghrita, evaluation of its antioxidant and anti-mycobacterial activity in tuberculosis. Methodology: This is a Pharmaceutico-analytical and Experimental study. Pharmaceutico-analytical study will be done at MGACH & RC, DMIHER Wardha and experimental work will be done at Central India Institute of Medical Sciences (CIIMS Nagpur).The study duration will be of 18 months. First, Nirgundi ghrita will be prepared as per Ayurvedic classical text and then will be subjected to analytical study as a part of standardization of formulation. Antioxidant study of Nirgundi ghrita will be done by using the DPPH free radical scavenging assay method. Evaluation of anti-mycobacterial activity of Nirgundi Ghrita will be done using BacT/ALERT 3D automated culture system. Discussion & Conclusion: PTB is one of the ancient diseases of human being, in spite of newer modalities for treatment of tuberculosis unfortunately, people are still suffering and it is among the top 10 killer infectious diseases. Considering the multi drug resistance and Adversarial effect of ATD, there is a need to develop alternative treatment module along with ATD. Hence the Ayurveda management helps to find out better treatment. Hence, Nirgundi Ghrita will be prepared to study their anti-mycobacterial activity in Tuberculosis and its antioxidant effect.